DLG5 P1371Q is associated with inflammatory bowel disease and complementary to R30Q in disease susceptibility (Swiss Medical Weekly, 2011)
BACKGROUND AND PURPOSE:The SNP R30Q (rs1248696) within the discs large homolog 5 (DLG5) gene has been associated with inflammatory bowel disease (IBD). In this study, we examined the genetic association of another DLG5 SNP P1371Q (rs2289310) with IBD and its interaction with R30Q in disease susceptibility. METHODS:A total of 213 IBD patients [106 familial; 59 Crohn’s disease (CD) and 47 ulcerative colitis (UC)] and 107 sporadic [57 CD and 50 UC] were included in this study. Controls included 139 non-diseased family members of IBD patients and 170 unrelated healthy subjects. Genotypes for P1371Q and G1066G polymorphisms were determined by PCR–based RFLP. Epistasis between P1371Q and R30Q in disease susceptibility was analysed using a novel statistical model. RESULTS:P1371Q was associated with IBD (OR = 2.335, 95% CI = 1.097–4.972, p = 0.0246), however, the synonymous variant G1066G (rs1648234) was not. Gender distribution analysis revealed the A allele of P1371Q was significantly associated with IBD in women (OR = 3.765, 95% CI = 1.307–10.85, p = 0.0095). Modeling interaction between P1371Q and R30Q showed a significant increase in disease association (OR = 2.265, 95% CI = 1.405–3.652, p = 0.0007) incidence for sporadic and familial IBD patients. Further epistatic analysis identified an increased significance in the association of gender with IBD (OR = 4.311, 95% CI = 2.101–8.846, p = 0.0001). CONCLUSIONS:DLG5 P1371Q was associated with IBD and this association was female-specific. A significant epistatic interaction between P1371Q and R30Q was observed, suggesting that P1371Q is complementary to R30Q, with R30Q exhibiting a dominant effect in IBD susceptibility.